The Effect of Shopping Lifestyle and Fashion Involvement on Purchase Decision with Impulse Buying as an Intervening Variable In E-commerce Shopee - Ayu Sari Dewi; Aida Nursanti; Marhadi Marhadi; Mida Aprilina Tarigan (IJEBA (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS), 2023)
This study aims to analyze the influence of shopping lifestyle and fashion involvement on purchasing decisions with impulse buying as an intervening variable on e-commerce shopee. This research was conducted on all consumers domiciled in Indonesia who had purchased products at Shopee e-commerce.In this study, it consists of four variables, namely one bound variable, one intervening variable, and two free variables. These variables are: Impulse Buying (Y2), Purchasing Decision (Y1), Fashion Involvement (X2), Shopping Lifestyle (X1). This study was conducted using a sample of 132 people with questionnaire crossing. The data analysis tool used for hypothesis testing is path analysis with a Partial Least Square (PLS) approach using the SmartPLS ver 3.0 software application. The results of this study state that: 1) shopping lifestyle has a positive and significant effect on impulse buying; 2) fashion involvement has a positive and significant effect on impulse buying; 3) Impulse buying has a positive and significant effect on the whiteness of the purchase; 4) shopping lifestyle has a positive and significant effect on purchasing options; 5) fashion involvement has a positive and significant effect on purchasing decisions; 6) shopping lifestyle has a positive and significant effect on purchasing decisions ventilated by impulse buying; 7) Fashion involvement has a positive and significant effect on purchasing decisions that are ventilated by impulse buying.